Entre promessas e realidade? As ações institucionalizadas de preservação da memória e do patrimônio cultural material de Bento Rodrigues e Paracatu de Baixo após o desastre ambiental - Vargas, Nayane Viale (2021)
The impacts on Bento Rodrigues and Paracatu de Baixo with the collapse of the Fundão dam were diverse, compromising the historical, architectural, artistic and cultural heritage of the Mariana region, Minas Gerais (MG), which is still home to riches from the times of Brazil-colony linked to religiosity and gold production. This research investigates, in the light of the Term of Transaction and Adjustment of Conduct, the reports of Program 12 of the Renova Foundation that discuss the actions taken to preserve the memory and material cultural heritage of the sub-districts of Bento Rodrigues and Paracatu de Baixo after the breakup. Of the Fundão dam (MG) in the period from 2016 to 2019. The methodological resources combine a bibliographic and documentary research, with a qualitative approach, guided by the categories: heritage, preservation, identity, place of memory and memory in the context of Information Science. The collapse of the Fundão dam caused several impacts on the cultural heritage of Bento Rodrigues and Paracatu de Baixo, places that brought together a rich history of the Brazilian colonial period. Thus, guaranteeing the preservation of the history and memory of the material cultural heritage of these sub-districts makes it possible to re-establish the affective and identity ties of a group. The results obtained showed partial elaboration of projects, inventories, fungus and bacteria disinfection process, restoration in sacred pieces, workshops and training with weak participation of the communities of Bento Rodrigues and Paracatu de Baixo, besides suggesting that the root of some problems about the material cultural heritage affected by the mud from the dam in the sub-districts surveyed are found in the Term of Transaction and Adjustment of Conduct, by configuring a subjective document in its content, limited to pointing out concrete ways to repair the damage.